Application Of Guided Inquiry Model to Learning Buffer Solution Material Chemistry to Improve Student Learning Outcomes - Rahmawati, Adisya; Nofiandari, Qotrunnasywa Ratri; Rahmawan, Setia (Jurnal Basicedu, 2025)
This study aims to find out how well the Guided Inquiry Learning (GIL) paradigm works to help students learn about buffer solutions in chemistry classes. To conduct a thorough literature analysis, 15 research publications examined the effects of GIL on many facets of student learning—such as conceptual knowledge, process skills, critical thinking, motivation, and attitude—. Compared to conventional teaching techniques, the results repeatedly show that the GIL model greatly enhanced student learning outcomes. In addition to developing critical thinking and problem-solving skills, students also showed a more excellent conceptual grasp of buffer solutions and improved scientific process skills (such as hypothesis development, data analysis, and inference). Furthermore, GIL fostered enhanced self-efficacy, better attitudes about learning, and higher levels of student motivation. The review also emphasizes how adaptable the GIL paradigm is, with successful outcomes from various implementations. These include virtual laboratories, LKS (Student Worksheets), LKPD (Learner Worksheets), and guided inquiry with diagrams. To improve learning experiences and attain better results in chemistry education, our findings highlight the significance of guided exploration, active student engagement, and collaborative learning.